The Urban Catharsis : Strategies for the adaptation of Johannesburg’s privately-owned public spaces along the mining belt. Approaches to the adaptation of mining landscapes for the leisurescape in Johannesburg south post-industry - Swart, Johan (University of Pretoria, 2020)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2019.